A COMPARATIVE LITERATURE ON CHILDREN'S SHORT STORIES - Muhammad Arief Budiman; Ikha Listyarini (LITE: Jurnal Bahasa, Sastra, dan Budaya, 2017)
There are many children’s short stories out there both in print media and e-media. This study proposes a comparison between Indonesian short stories in print media and American short stories in e-media. This research is qualitative and descriptive. The subject of research is eleven short stories, i.e. seven print-media Indonesian short stories and four e-media American short stories. The data collection method used is documentation and the data are analysed by using the Miles and Huberman techniques. The results indicate that the eleven children short stories carry good values that are in accordance with the character teaching, character building, and character shaping. One children’s short story teaches being helpful and caring for the environment and people around us while theothers teach being persistent and not easily giving up despite your failures.There is also a story that teaches being humble and not being arrogant. It is also found that the teaching is not always for the children, it could also be for the adults just like in one of the stories that teaches the adults for being patient in facing and handling the naughty children.Keywords: children short stories, comparative literature, character building